+0  
 
0
282
1
avatar

(d-1)/5 = (d-3)/3

 

Solve the equation 

Guest Apr 6, 2017
 #1
avatar+7266 
+3

\(\frac{d-1}{5}=\frac{d-3}{3}\)

 

Cross-multiply.

\((3)(d-1)=(5)(d-3)\)

 

Distribute.

\(3d-3=5d-15\)

 

Subtract 3d from both sides.

\(-3=5d-3d-15\)

 

Add 15 to both sides.

\(-3+15=5d-3d \\~\\ 12=2d\)

 

Divide both sides by 2.

\(\frac{12}{2}=d \\~\\ 6=d\)

hectictar  Apr 6, 2017

16 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.